1986
DOI: 10.1246/cl.1986.863
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICALLY PREPARED POLY(N-METHYLPYRROLE) THIN FILM. ITS APPLICATION TO THE FIELD-EFFECT TRANSISTOR

Abstract: A thin film of poly(N-methylpyrrole) has been prepared by a chemical method. The chemical structure of the polymer resembles that of the electrochemically prepared one. A fild-effect transistor has been fabricated utilizing the polymer as a semiconducting material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Polymers and copolymers based on pyrrole, furan, and especially thiophene have been under investigation for some years. They possess interesting electrical, optical, and electrochemical properties and are promising materials for field-effect transistors and many other potential applications. , It has been found that the band gap of polyheterocycles decreases linearly with the amount of quinoid structure the polymer can assume upon doping. Thus, variation of the heteroatom allows control of the electronic and mechanical properties of the polymer. , Due to controlled chain and conjugation length, and the higher regularity and homogeneity of the chain structure without mislinkages and cross-linkings, oligomers can reach or exceed the properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers and copolymers based on pyrrole, furan, and especially thiophene have been under investigation for some years. They possess interesting electrical, optical, and electrochemical properties and are promising materials for field-effect transistors and many other potential applications. , It has been found that the band gap of polyheterocycles decreases linearly with the amount of quinoid structure the polymer can assume upon doping. Thus, variation of the heteroatom allows control of the electronic and mechanical properties of the polymer. , Due to controlled chain and conjugation length, and the higher regularity and homogeneity of the chain structure without mislinkages and cross-linkings, oligomers can reach or exceed the properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…They possess interesting electrical, optical, and electrochemical properties and are promising materials for field-effect transistors and many other potential applications. 1,2 It has been found that the band gap of polyheterocycles decreases linearly with the amount of quinoid structure the polymer can assume upon doping. Thus, variation of the heteroatom allows control of the electronic and mechanical properties of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…conductivity of these materials provides potential applications in fabricating many kinds of microelectrical devices (7)(8)(9)(10)(11)(12). However, most electrically conductive polymers are brittle and have low mechanical strengths (1 3).…”
mentioning
confidence: 99%
“…'*2 Polymers in the semiconducting regime can be expected to be used conveniently to fabricate semiconducting devices such as Schottky-type junction diodes3, and field effect transistors (FET). 5 Recently, perchlorate ion (Cloy) doped polypyrrole and poly(N-methylpyrrole) (PNP) have been reported to make excellent Schottky-type junctions with low work-function metals such as i n d i~m .~.~ It has been reported that heat treatment of the polymer in air before In-metal deposition stabilizes the diode. I t has been confirmed by x-ray photoemission spectroscopy (XPS)' and by tunnel Schottky analysis4 that the existence of a composite layer of a few angstroms at the interface between the In electrode and the conducting polymer plays a significant role.…”
Section: Introductionmentioning
confidence: 99%